Nomina Bahasa Melayu Riau Dialek Kampar: Tinjauan Bentuk Morfologis - S, Ermawati.; Hermaliza, Hermaliza (GERAM: Gerakan Aktif Menulis, 2019)
The research entitled "Riau Malay Language, Kampar Dialect: Overview of Morphological Forms" was motivated by minor attention of Kampar society, especially the younger generation towards the language. The phenomenon happened because of the cultural assimilation of the Kampar society with other communities. Moreover, there were exiguous observers of the Riau Malay Language of Kampar dialect. Therefore, this research was conducted with the purpose of describing the basic nouns and nouns derivation from the Riau Malay language Kampar Dialect: An Overview of Morphological Forms. This Research was considerable to be done to find out the background of life and culture that is closely related to government programs to preserve the regional culture in Indonesia. This research was also expected relevant for the development and research of languages which are feared to be extinct if they are not published since now. In addition, it supported the fostering and development of national languages, especially in the enrichment and vocabulary of Indonesian languages as well as documenting the Malay language profile of the Kampar dialect so that it does not experience a shift or even extinction. This research was a qualitative type of field research and uses ethnographic methods. This research was conducted in Muara Selaya Village, Kampar Kiri District, Kampar Riau Regency. Research data in the form of words gathered from the informant's speech. Data collection were done by observation, record, see competent involvement, collaboration. Analyzing the data were done by reducing, presenting data, and drawing final conclusions. The results of this study were basic nouns consisting of general basic nouns and special basic nouns such as ayi ‘water', asoʔ 'smoke', ujan ' rainy ', anjiʸaŋ 'dog', and padusi 'female' while Malay nouns derived from the Kampar dialect Malay among them -an in Aŋsuŋan 'instalment payment', -wan in Baŋsawan 'aristocrats', ka-an in the kacomean 'anxiety', ke-an in kelurahan administrative village‘, pe- in petani 'farmer', pa- in padagang 'merchant, pany- in panyogan ' lazy‘, and pa-an in pajonjiyan 'agreement'.